KARANG TARUNA COUNSELING PROGRAM TO INCREASE ITS ROLE AND CREATIVITY - Nina Dwiastuty; Ira Miranti; Noni Marlianingsih (Journal of English Language Studies, 2016)
Youth is a pioneer for the progress of Indonesian because youth is the next generation that should have a broad range of knowledge and skills together with firm principle. Young people have to be built and directed so that his role can be beneficial. Similarly, with the youth in the region of RT. 02 and 03 Cibeureum Village, the majority of the young people are very religious because 85% of youth that is living in this region are mostly pesantren alumni. However, the youth only has the ability and knowledge for themselves and not to society. In this village, young people join the Karang Taruna activity and Ikatan Remaja Masjid (IRMACH), but they are more active in religious activities so that this management organization is a need to be developed and nurtured to make the young people in this region became more active and creative in other aspects. For that reason, we carry out counseling to youth in the RT.02 and 03 so that they can perform the function and role as a part of the society to build community life with creativity. This activity was attended by 25 young people from the two regions RT. 02 and 03 Cibeureum Village, Cisarua District. Keywords: counseling; creativity; young people; roles